IMPLEMENTATION OF A FINGERPRINT ELECTRONIC ATTENDANCE POLICY AS A SUPPORT FOR EMPLOYEE WORK DISCIPLINE AT THE BUSINESS MANAGEMENT AGENCY (BPU) OF GORONTALO STATE UNIVERSITY - Melani, Marcely; Ilato, Rosman; Tantu, Romy (Public Policy Journal, 2024)
This study aims to determine and describe (1) the implementation of the fingerprint electronic attendance policy as a support for employee work discipline at the Business Management Agency (BPU) of Gorontalo State University, which is studied from: 1. planning, 2. implementation, and 3. evaluation. (2) Determining Factors for the Success of the Implementation of the Finger Print Electronic Attendance Policy as a Support for Employee Work Discipline at the Business Management Agency (BPU) of Gorontalo State University, which are studied from: 1. Apparatus Compliance; 2. Smooth Absence of Problems; and 3. Satisfactory Performance. The approach used in this study is qualitative with descriptive qualitative methods. Data collection using interviews, observation, and documentation The results of this study show that (1) the implementation of the Fingerprint Electronic Attendance Policy (Fingerprint) as a Support for Employee Work Discipline at the Business Management Agency (BPU) of Gorontalo State University has run quite optimally. This is shown by the existence of a) planning, b) implementation, and c) evaluation that has been carried out based on the regulation of the Rector of Gorontalo State University Number 1,786 / UN47. A2/KP/2022 on July 25, 2022, to increase discipline, productivity, and work effectiveness, as well as working hours for civil servants in education and contract personnel within Gorontalo State University. Determining Factors for the Success of the Implementation of the Electronic Attendance Policy Fingerprint (Fingerprint) as a Support for Employee Work Discipline at the Business Management Agency (BPU) of Gorontalo State University based on the results of research conducted that has run optimally. This can be seen from a) apparatus compliance; employees at the Business Management Agency have shown compliance with regulations related to the use of electronic attendance to improve employee discipline, b) smoothness factors, the use of electronic attendance systems can increase the effectiveness in managing attendance administration as a guideline for employee benefits, c) satisfactory performance, employee performance, and productivity are increasing with the innovation of changes. The previous attendance method was still manual, despite technology